MODERASI BERAGAMA SEBAGAI RESPON BIJAK DI TENGAH WABAH COVID-19 - Khabib Musthofa (Profetika: Jurnal Studi Islam, 2021)
The article tries to describe the response of the Indonesian people in addressing the Covid-19 outbreak. Starting from the response that considers that this epidemic has prevented them from worshiping Allah, to the excessive response of health initiatives to buying up the attributes of health protocols (masks, handsanitizers) which result in scarcity to expensive items for their own personal and group interests. This phenomenon is actually not in line with the message of religious moderation which contains fair values, tawazzun; balanced, tolerant and moderate. In a pandemic situation like today, religious moderation is something that must be maximized in dealing with this abnormal situation. This is because Covid 19 is a virus that does not choose its target based on considerations of self-righteousness, religion, ethnicity and culture and sect. Each individual has the potential to be infected if the body's resistance and condition are not strong, do not adopt a healthy lifestyle or do not maintain a distance (physical distancing). Abstrak: Artikel ini mencoba menggambarkan respon masyarakat Indonesia dalam menyikapi wabah covid-19. Mulai dari response yang menganggap wabah ini telah menghalangi mereka dari beribadah kepada Allah, hingga respon ikhtiar kesehatan dengan berlebihan hingga memborong atribut protokol kesehatan (masker, handsanitizer) yang mengakibatkan kelangkaan hingga mahal barang tersebut demi kepentingan pribadi dan kelompoknya sendiri. Fenomena tersebut sejatinya tidak sejalan dengan pesan moderasi beragama yang mengandung nilai-nilai adil, tawazzun;  seimbang, tolerir dan moderat. situasi pandemi seperti saat ini moderasi beragama menjadi sesuatu yang mutlak dimaksimalkan dalam menghadapi situasi yang tidak normal tersebut. Dikarenakan Covid 19 merupakan virus yang tidak memilih targetnya berdasarkan pertimbangan kesalihan diri, agama, suku dan budaya serta aliran. Setiap individu berpotensi terjangkit apabila ketahanan dan kondisi tubuh tidak kuat, tidak menerapkan pola hidup sehat atau tidak menjaga jarak (phsysical distancing).